Risk Analysis on the Implementation and Operation of Green Hydrogen and Its Derivatives in the Spanish Port System - Daniel García Nielsen; Alberto Camarero-Orive; Javier Vaca-Cabrero; Nicoletta González-Cancelas (Future Transportation)
The problem addressed in this paper is the identification and management of risks associated with the implementation and operation of green hydrogen in the Spanish port system. The growing demand for clean energy and environmental regulations are driving the adoption of green hydrogen as a viable solution to decarbonize shipping. However, this transition comes with significant challenges, including safety, infrastructure, and hydrogen handling risks. In the existing literature, several authors have used methodologies such as qualitative and quantitative risk analysis, techniques such as FMEA (Failure Modes and Effects Analysis), and the evaluation of impacts and probabilities of occurrence to identify and manage risks in similar projects. These approaches have made it possible to identify potential threats and propose effective mitigation measures. In this work, a combined methodology is proposed that includes the identification of threats, risk assessment through risk matrices, and classification of these risks for their proper management. The SWIFT method (Structured What-If Technique) and the use of impact-probability matrices are applied. The main conclusion of the work is that, although green hydrogen has great potential for the decarbonization of the port sector, its implementation requires careful management of the risks identified. The proposed mitigation measures are essential to ensure the safety and viability of green hydrogen projects in Spanish ports.